Study demands and health status among medical students in two German universities - Voss, Amanda Sophie; Dettmer, Susanne; Tschorn, Mira; Zoellick, Jan C. (Journal of Public Health, 2024)
Aim: Medical students regularly report high study demands and low mental health. Both demands and mental health can be influenced by the curricular structure of degree programmes. We thus studied medical students in two different curricula in Germany, investigating their study demands, study and life satisfaction, and overall and mental health, with emphasis on contrasting beginners and advanced students. Subject and methods: We used online surveys with convenience samples through university mailing lists and student union channels. Uni1 participants (N = 357; 70% female; M = 24.83 years) were older than Uni2 participants (N = 126; 79% female; M = 23.39 years), but the cohorts did not differ further regarding sociodemographic variables. The main outcomes were study demands on six dimensions, study and life satisfaction, and overall and mental health. For analyses, we used t-tests for comparisons and correlations for associations. Results: Students of both universities reported good mental and overall health as well as high satisfaction with their studies and lives, although sleep difficulties were prevalent. Study demands were low to medium, with the highest demands being learning activities (M = 5.31; SD = 2.19, scale 0–10), self-structuring (M = 4.61; SD = 2.01), and performance pressure (M = 4.45; SD = 2.27). The students in the reformed degree programme reported fewer issues with integrating theory and practice than those in the regular degree programme (MUni1 = 3.38; SDUni1 = 2.05; MUni2 = 4.17; SDUni2 = 2.06; t(430) = −3.53, p <.001). Conclusion: Our sample was rather resilient regarding mental health and coping with study demands. The two universities showed little to no differences. With relative increased demands regarding learning activities, self-structuring, and performance pressure, we suggest focusing on learning strategies for beginners and strategies for stress reduction to address, among other things, the reported sleep difficulties.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Medical students; Mental and overall health; Online survey; Stress; Student satisfaction; Study demands